1983
DOI: 10.3133/ofr83542
|View full text |Cite
|
Sign up to set email alerts
|

Sources and mechanisms of recharge for ground water in the west-central Amargosa Desert, Nevada– A geochemical interpretation

Abstract: Ground water in the west-central Amargosa Desert, Nevada, was recharged primarily by overland flow of snowmelt in or near the present-day stream channels, rather than by subsurface flow from highland recharge areas to the north. Geochemical arguments, including reaction mechanisms, are used to support these findings. Carbon-, hydrogen-, and oxygen-isotope data show that much of the recharge in the area occurred during late Wisconsin time. Absence of ground water recharged prior to late Pleistocene is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 11 publications
1
87
1
Order By: Relevance
“…They used Isotopic data to conclude that groundwater from Pahute Mesa discharges through tuffaceous aquifers Into Oasis Valley, but not Into Fortymtle Wash. They also concluded that water In the alluvium In the upper north-central Amargosa Desert originated principally as groundwater In tuffs In Fortymlle Wash; this disagrees with the conclusion of Claassen (1985) that overland flow was more Important. White and Chuma (1986) Infer that, during passage through Oasis Valley, dissolved carbonate In the water Is exchanged with soil-zone carbon dioxide and carbonate In caliche; this exchange Is facilitated by the proximity of the water to ths ground surface In Oasis Valley.…”
mentioning
confidence: 50%
See 3 more Smart Citations
“…They used Isotopic data to conclude that groundwater from Pahute Mesa discharges through tuffaceous aquifers Into Oasis Valley, but not Into Fortymtle Wash. They also concluded that water In the alluvium In the upper north-central Amargosa Desert originated principally as groundwater In tuffs In Fortymlle Wash; this disagrees with the conclusion of Claassen (1985) that overland flow was more Important. White and Chuma (1986) Infer that, during passage through Oasis Valley, dissolved carbonate In the water Is exchanged with soil-zone carbon dioxide and carbonate In caliche; this exchange Is facilitated by the proximity of the water to ths ground surface In Oasis Valley.…”
mentioning
confidence: 50%
“…The straight Hne through the origin, with a slope of 0.82, represents a least squares fit of all the data. Claassen (1985) shows a similar plot with a line representing evaporation of modern precipitation; the slope of that line is approximately 1.65, that 1s, twice the slope of the line In F1g. 13(a).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Hydrogeochemical analyses of the formation waters in the carbonate aquifers reveal a narrow range of 13-16 ohm-m for the fluid resistivities from springs in the Ash Meadows discharge zone [Winograd and Thordarson, 1975]. From additional geochemical analyses of water sampled in boreholes near Ash Meadows [Claassen, 1985], we calculated a water resistivity of 9.4 ohm-m and therefore conclude that 10 ohm-m is a reasonable average resistivity for zones 2, 4, 6, and 7. Models relating fluid resistivity and rock resistivity have the form:…”
Section: Discussionmentioning
confidence: 96%